Tinjauan Hukum terhadap Ketiadaan Ketentuan Uang Pisah dalam Perjanjian Kerja Bersama: Implikasi bagi Pekerja dan Pengusaha - Sulkiah Hendrawati; Wahyudi Wahyudi; Mohamad Ali (Jurnal Hukum Lex Generalis, 2025)
This study's goal is to look into the legal provisions concerning severance pay (uang pisah) in employment relationships in Indonesia, particularly in the context of Collective Labor Agreements (PKB), and to review the legal implications from the absence of severance pay clauses in such agreements on the protection of workers’ rights and employers’ obligations. Furthermore, this study presents a legal analysis of the judicial considerations of the Industrial Relations Court in Yogyakarta in Decision No. 19/Pdt.Sus-PHI/2022/PN Yyk. Using a normative juridical approach and qualitative analysis, the findings reveal that Indonesian labor regulations do not explicitly determine the amount of severance pay, instead delegating such provisions to be negotiated in the PKB. The absence of such provisions creates a legal vacuum that leads to uncertainty in the safeguarding of labor rights. In its decision, the court interpreted the right to severance pay based on principles of justice and the worker's length of service, despite its absence in the PKB. This highlights the urgency of establishing clear and explicit regulations on severance pay within collective labor agreements to ensure balanced and equitable legal protection for both parties.